Characteristic of Red Blood Cell Profile as a Predictor of 30-Day Clinical Outcome in Ischemic Stroke Patients - Nathania Fadjarsugeng; Rizaldy Taslim Pinzon; Sugianto Sugianto (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2022)
Ischemic stroke is the most common type of stroke in Indonesia. Measuring inflammatory biomarkers (IL-6) is a way to predict clinical outcomes in ischemic stroke patients. However, the laboratory test is very expensive, so it requires another test that can represent the inflammation, for instance, by measuring RDW and MCV value when hospitalized. Hence, this study aims to measure RDW and MCV value of ischemic stroke patients at admission with a 30-day clinical outcome (disability). This study is a retrospective cohort that used secondary data from medical records of ischemic stroke patients in Bethesda Hospital Yogyakarta and was conducted on 105 subjects. They are divided into two groups by their mRS score in 30-day after onset, (1) the independent group (mRS score of 0- 2), (2) the dependent group (mRS score of 3-6). After that, these two groups are analyzed by an independent t-test. High RDW and low MCV value at admission increased 30-day disability risk. There was a statistically significant RDW value and 30-day clinical outcome (p=0,008), but there was no statistically significant MCV value and 30-day clinical outcome (p=0,277). 30-day clinical outcome in ischemic stroke patients can be predicted by their characteristic of red blood cell profile at admission.